Legal Analysis of Criminal Liability of Land Deed Officials (PPAT) for Land Document Engineering (Study of West Jakarta District Court Decision Number 248/Pid.B/2022) - Rahmat Tri Andika Debataraja; Janpatar Simamora; Januari Sihotang (Universitas Islam Sultan Agung, 2026)
This study aims to analyze the criminal liability of Land Deed Officials (PPAT) in the fabrication of land documents as well as the supervision and prevention efforts based on the West Jakarta District Court Decision Number 248/Pid.B/2022. The issues studied include the form of criminal liability of PPAT involved in falsification or manipulation of land documents and the effectiveness of the supervision mechanism by the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency. The research method used is normative legal research with a statutory approach and a case approach, and analyzed qualitatively. The results of the study indicate that PPAT can be held criminally responsible if proven to have intentionally participated in the act of authentic deeds. In addition, administrative supervision of PPAT still faces various obstacles, so it is necessary to strengthen the supervision system, increase professionalism, and enforce strict sanctions to prevent the recurrence of the practice of fabricating land documents.